Nurses’ Turnover Intentions in Private Hospitals: A Narrative Study - Novia Sabatini, Monika Steffi; Dwiantoro, Luky; Dewi, Nur Setiawati (Gaceta Médica de Caracas, 2023)
Objective: This study aims to analyze the problems often faced by nurses with a holistic approach to identifying the main motivations or reasons why nursing staff intends to move from the hospital where they work. Methods: This research was conducted by using a qualitative method with a narrative study approach using semi-structured interviews where one participant will be given guideline questions and 8 responsive assessments that will be given to respondents where the assessment has previously gone through the expert test stage.